The Emerging Roles of Rad51 in Cancer and Its Potential as a Therapeutic Target - Wang, Ziyi; Jia, Renxiang; Wang, Linlin; Yang, Qiwei; Hu, Xiaohai; Fu, Qiang; Zhang, Xinyu; Li, Wenya; Ren, Yi (Frontiers in Oncology, 2022)
Defects in DNA repair pathways are emerging hallmarks of cancer. Accurate DNA repair and replication are essential for genomic stability. Cancer cells require residual DNA repair capabilities to repair the damage from replication stress and genotoxic anti-tumor agents. And the defective DNA repair also promotes the accumulation of genomic changes that eventually lead to tumorigenesis, tumor progression, and therapeutic resistance to DNA-damaging anti-tumor agents. The Rad51 recombinase is a critical effector of Homologous Recombination, which is an essential DNA repair mechanism for double-strand breaks. Rad51 has been found to be upregulated in many malignant solid tumors, and correlated with poor prognosis. In multiple tumor types, Rad51 is critical for tumor metabolism, metastasis and drug resistance. Herein, we initially introduced the regulation of Rad51 expression. Additionally, we primarily discussed the role of Rad51 in DNA repair, tumor metabolism, metastasis, resistance to chemotherapeutic agents and poly-ADP ribose polymerase inhibitors.